The morphological and immunohistochemical spectrum of gastric biopsies of patients with absorptive hypercalciuria. Issue 1 (1st January 2015) - Declich, Paolo; Belloni, Jacopo; Tavani, Enrico; Omazzi, Barbara; Bellone, Stefano; Bortoli, Aurora; Arena, Ilaria; Devani, Massimo
Abstract : Objective: Idiopathic hypercalciuria is characterised by renal stone formation and vertebral osteoporosis. The syndrome displays high clinical variability with patients almost equally distributed between fasting or renal type (prevalent calcium loss) and absorptive type (prevalent increase of intestinal absorption). Absorptive hypercalciuria (AH) is characterised by hypersensitivity of calcium-sensing receptors of antral G cells with normal fasting gastrinaemia and meal hypergastrinaemia. To the best of our knowledge, no study has been published about the morphological aspects of gastric biopsies of patients with AH and the immunohistochemical findings of gastrin-producing G cells. So we studied morphologically and immunohistochemically a group of 38 patients with AH, describing their gastric findings and associated lesion. Design: All 38 patients had a clinical-laboratory diagnosis of AH with normal fasting hypergastrinaemia and an abnormal rise of gastrinaemia after a standardised meal test. Their 38 antral and 27 body-fundus biopsies, and 5 normal antral and body controls, were stained with H&E, Giemsa stain, polyclonal antiserum anti-Gastrin and a monoclonal antibody anti-Chromogranin A. Results: Antral biopsies of all 38 patients showed a simple (15) or linear (23) hyperplasia of G cells, whereas only 2 of 27 body biopsies showed a nodular hyperplasia of endocrine cells. In five patients with AH, we found an association with fundic gland polyps (FGPs). Conclusions: We found in all of the patients with AH a correlation between meal hypergastrinaemia and morphological antral G-cell hyperplasia. Moreover, in five patients, AH was associated with FGPs. We know from literature data that FGPs' development in Zollinger-Ellison syndrome is statistically associated with hypergastrinaemia. From our present data, we suggest that even in AH the stimulated hypergastrinaemia may have a role in polyp development.